Impact of Price, Brand Image and Product Quality on Purchase Decisions in the Hexohm Bengkulu Vape Community - Hafiz Agung Rasuma; Ida Ayu Made E. Gayatri; M.Rahman Febliansa (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine the effect of price, brand image and product quality on purchasing decisions in the Bengkulu Hexohm vape community. This research is quantitative descriptive. The method used is a questionnaire method. The sample of this study was 100 respondents in the Bengkulu Hexohm vape community. The results of multiple linear regression show that Y = 21.251+0.672 (X1)+ 0.174 (X2) + 0.450 (X3) + 9.735, that the regression coefficient is positive, meaning that there is a positive or unidirectional relationship between price, brand image and product quality on the Vape Community Hexohm Bengkulu. The results of the price test (X1) show tcount 3,007 > ttable 1,660 and a significance of 0,003 < 0,05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning that the price (X1) has a positive and significant effect on purchasing decisions (Y) in the Hexohm Vape Community Bengkulu . The results of the brand image test (X2) show tcount 0.688 < ttable 1,660 and significance 0.493 > 0.05, then the results of the hypothesis Ha are rejected and Ho is accepted, meaning that brand image (X2) has no effect on purchasing decisions (Y) in the Hexohm Vape Community Bengkulu . The results of the product quality test (X3) show tcount 5.742 > ttable 1,660 and significance 0.000 <0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, meaning product quality (X3) has a positive and significant effect on purchasing decisions (Y) in the Vape Community Hexohm Bengkulu. The result of the Fcount value is greater than the Ftable value, which is 12.807 > 2.70, so it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between price (X1), brand image (X2) and product quality (X3) on the purchasing decision variable (Y). This can be seen at the significance level of 0.000 < 0.05.